Design and Performance Analysis of a SolidWorks-Based Disk Mill Coffee Grinder for MSMEs - Franklin Taruyun Hudeardo Sinaga; Eka Putra Dairi Boangmanalu; Jandri Fan HT Saragi; Angga Bahri Pratama; Al Qodry (International Journal of Business and Quality Research, 2026)
This study presents the design, fabrication, and performance analysis of a SolidWorks-based disk mill coffee grinder specifically developed for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia's expanding coffee industry. Addressing the technological gap between industrial-scale equipment and small-enterprise operational constraints, the research employed parametric 3D modeling and virtual assembly simulation to optimize machine configuration prior to physical fabrication. The design integrates a 5.5 HP gasoline engine with a 3:1 pulley reduction system, angle iron frame structure (600×600×730 mm), and adjustable pin-type grinding disks to achieve targeted processing capacity and particle uniformity. Performance testing demonstrated that the machine successfully processes 1 kg of roasted coffee beans in approximately 8 minutes, yielding a theoretical throughput of 30 kg/hour with consistent particle distribution suitable for various brewing methods. Material loss was maintained below 2%, while operational vibration and noise levels remained within acceptable limits for workshop environments. The SolidWorks-driven design methodology significantly reduced material waste and iterative physical modifications by enabling early detection of interference conflicts and spatial optimization during the digital prototyping phase. These findings confirm that CAD-integrated engineering approaches can effectively support the development of cost-effective, maintainable, and scalable processing equipment tailored to MSME requirements. The resulting disk mill configuration offers a practical solution for enhancing product consistency, operational efficiency, and competitive positioning within Indonesia's decentralized coffee value chain, while providing a replicable framework for localized agricultural machinery innovation.